(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT Research approaches of a language are interrelated with each based on the requirements and aspects of a linguistic research. Scholars of language and linguists are familiar with several linguistic research approaches; Such as historical, descriptive and comparative approaches …etc. Those approaches interrelate with each other while researching and investigating a topic. Hence, it is necessary for a researcher to be, relatively, familiar with these approaches, so he can employ them to unveil secrets of a language and thus achieving the research’s goal.